Sentinel lymph node biopsy experience in squamous cell carcinoma of the oral mucosa сT1–2N0M0 - F. E. Sevryukov; V. V. Polkin; Yu. A. Panaseikin; M. A. Sigov; R. F. Zibirov; I. A. Bekhtereva; S. A. Ivanov; A. D. Kaprin (Опухоли головы и шеи)
Introduction. Head and neck cancer is the 7th most common malignancy worldwide; squamous cell carcinoma of the oral mucosa are almost a third of tumors of that localization. Metastatic lesions of the neck lymph nodes are an unfavorable prognostic factor for malignant tumors of that location since it is associated with a 50 % decrease in overall survival. In this regard, the detection of metastases to the neck lymph nodes is an important component of high-quality oncological care for patients with that pathology.Aim. To evaluate the efficiency of sentinel lymph node biopsy in squamous cell carcinoma of cavity of mouth mucosa cT1–2N0М0.Materials and methods. 72 patients were included in trial at the age from 21 to 74 (mean 57.3) with confirmed squamous cell carcinoma of cavity of mouth mucosa cT1–2N0М0. No evidence of regional metastasis, by preoperative examination, including ultrasound, computed tomography with intravenous contrast was observed. All patients received radioisotope research to determine localization of sentinel lymph nodes, and then biopsy of that nodes was performed. Before obtaining information about the status of the sentinel lymph node, radical neck dissection was not performed. Pathology report with immunohistochemical investigation was performed by pathologist of A. F. Tsyb Medical Radiological Research Center – branch of the National Medical Research Radiological Center, Ministry of Health of Russia.Results. When assessing efficiency of sentinel lymph node method, true positives results (detection of metastasis in sentinel lymph node) were achieved in 3 (4.17 %) out of 72 cases. Follow up time was from 1 to 69 months. Among those cases, where metastasis in sentinel lymph nodes were not detected, relapse in regional lymph nodes was developed in 3 (4.35 %) out of 69 cases. Radical neck dissection was performed in cases with metastasis in sentinel lymph nodes. The specificity of method was 95 %, the predictive value of a negative result was 0.04.Conclusion. Sentinel lymph neck node biopsy is an effective method of subclinical locoregional metastases detection in cancer of oral mucosa cT1–2N0M0. In our study of sentinel lymph neck node biopsy, oncological outcomes were comparable to radical neck dissection, with fewer postoperative complications.